The Business Impact of Learning: A Healthcare Case Study - Battista, Alexis; Rooij, Shahron Williams van (Journal of Applied Business and Economics, 2018)
Using an embedded, single-case study, this paper explores learning opportunities in a worksite healthcare services firm and how the business impact of employee learning is measured. We applied grounded theory analytical procedures, with an eye to developing a theoretical model of the impact measurement process. The resulting model illustrates how practical issues created a fixed focus on clinical and regulatory requirements, inhibiting consensus about what constitutes learning impact measurement and the extent to which non-technical learning is valued in identifying employees for development and advancement. Lastly, we discuss implications for decision-makers in similar organizations.